2000
DOI: 10.1073/pnas.040552897
|View full text |Cite
|
Sign up to set email alerts
|

The protease thrombin is an endogenous mediator of hippocampal neuroprotection against ischemia at low concentrations but causes degeneration at high concentrations

Abstract: We have considered the extracellular serine protease thrombin and its receptor as endogenous mediators of neuronal protection against brain ischemia. Exposure of gerbils to prior mild ischemic insults, here two relatively short-lasting occlusions (2 min) of both common carotid arteries applied at 1-day intervals 2 days before a severe occlusion (6 min), caused a robust ischemic tolerance of hippocampal CA1 neurons. This resistance was impaired if the specific thrombin inhibitor hirudin was injected intracerebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
265
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 270 publications
(276 citation statements)
references
References 26 publications
10
265
1
Order By: Relevance
“…The possible involvement of mesotrypsin in these processes in the brain through the PARs system can be supported by our data demonstrating the potency of mesotrypsin to activate PAR-1 in human astrocytoma cells. If the knowledge on this new PAR-1 agonist in the brain would be extended, mesotrypsin could be considered as another signaling molecule in the brain acting via PAR-1, in addition to thrombin (Striggow et al, 2000). Our findings could imply involvement of mesotrypsin in protection/degeneration or plasticity processes in the human brain for which serine proteases are known to be important (Yoshida & Shiosaka, 1999;Vergnolle et al, 2003;Rohatgi et al, 2004).…”
Section: Discussionmentioning
confidence: 75%
“…The possible involvement of mesotrypsin in these processes in the brain through the PARs system can be supported by our data demonstrating the potency of mesotrypsin to activate PAR-1 in human astrocytoma cells. If the knowledge on this new PAR-1 agonist in the brain would be extended, mesotrypsin could be considered as another signaling molecule in the brain acting via PAR-1, in addition to thrombin (Striggow et al, 2000). Our findings could imply involvement of mesotrypsin in protection/degeneration or plasticity processes in the human brain for which serine proteases are known to be important (Yoshida & Shiosaka, 1999;Vergnolle et al, 2003;Rohatgi et al, 2004).…”
Section: Discussionmentioning
confidence: 75%
“…Thrombin is a key mediator of edema formation and cell death in experimental stroke [26,37,41]. Recent evidence also suggests that thrombin may modulate brain injury in Parkinson's disease (PD).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, while having blood-clotting, woundhealing and, at low dose, neuroprotective properties (40), thrombin was also reported to have a profound neurotoxic potential (1,5). Several studies revealed impairment of neuronal populations upon thrombin exposure (10,13,19,35,40). Cytokines could play a critical role in these in vivo scenarios.…”
Section: Thrombin As An Assumed Activator Of Microglial Releasementioning
confidence: 99%